2017
DOI: 10.1111/coa.12859
|View full text |Cite
|
Sign up to set email alerts
|

Peak nasal inspiratory flow correlates with quality of life in functional endoscopic sinus surgery

Abstract: Changes in PNIF after FESS appear to best reflect improvements in quality of life in CRS as measured using the "SNOT-22" questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 24 publications
2
25
0
1
Order By: Relevance
“…Five RCTs [14][15][16][17][18] and 25 RWE studies 65 reported mean baseline SNOT-22 scores in the moderate range. Five RCTs [19][20][21][22][23] and 17 RWE studies [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] reported severe mean baseline SNOT-22 scores. These findings were consistent with the treatment plan for CRSwNP provided by Fokkens et al 92 , which recommended surgery as treatment for patients with more severe symptoms or with polyps that are recalcitrant to medical management.…”
Section: Stratification Of Snot-22 Scores Prior To Surgerymentioning
confidence: 99%
“…Five RCTs [14][15][16][17][18] and 25 RWE studies 65 reported mean baseline SNOT-22 scores in the moderate range. Five RCTs [19][20][21][22][23] and 17 RWE studies [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] reported severe mean baseline SNOT-22 scores. These findings were consistent with the treatment plan for CRSwNP provided by Fokkens et al 92 , which recommended surgery as treatment for patients with more severe symptoms or with polyps that are recalcitrant to medical management.…”
Section: Stratification Of Snot-22 Scores Prior To Surgerymentioning
confidence: 99%
“…It could therefore be argued that the inferior turbinate being the larger structure and more involved with the nasal vascular regulated nasal cycle will also result in greater postdecongestant changes. Conversely, bilateral NIPF has been shown to significantly increase following functional endoscopic sinus surgery (FESS) in addition to correlating with improved quality of life in patients [31] which would imply that more drastic treatment regimens would be required to see a change in NIPF in CRS. Another study did suggest that CRS patients may require a more long term course of decongestants to be effective, compared to allergic rhinitis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-and post-decongestion testing can distinguish between nasal obstruction due to soft tissue and that due to fixed structural deformity (249,332,333) (Table 6). This can be useful in the appropriate selection of surgical procedures (314,334) as well as in the evaluation of nasal surgery outcomes (288,289,(334)(335)(336)(337)(338)(339)(340)(341) .…”
Section: Usesmentioning
confidence: 99%